Co‐delivery of dendritic cell vaccine and anti‐PD‐1 antibody with cryomicroneedles for combinational immunotherapy - Hao Chang; Xueyu Wen; Zhiming Li; Zhixin Ling; Yanting Zheng; Chenjie Xu (Wiley, 2023)
Abstract Combinational immunotherapy of dendritic cell (DC) vaccines and anti‐programmed cell death protein 1 antibodies (aPD1) has been regarded as a promising strategy for cancer treatment because it not only induces tumor‐specific T cell immune responses, but also prevents failure of T cell functions by the immune suppressive milieu of tumors. Microneedles have emerged as an innovative platform for efficient transdermal immunotherapies. However, co‐delivery of DC vaccines and aPD1 via microneedles has not been studied since conventional microneedle platforms are unsuitable for fragile therapeutics like living cells and antibodies. This study employs our newly invented cryomicroneedles (cryoMNs) to co‐deliver DC vaccines and aPD1 for the combinational immunotherapy. CryoMNs are fabricated by stepwise cryogenic micromoulding of cryogenic medium with pre‐suspended DCs and aPD1, which are further integrated with a homemade handle for convenient application. The viability of DCs in cryoMNs remains above 85%. CryoMNs are mechanically strong enough to insert into porcine and mouse skin, successfully releasing DCs and aPD1 inside skin tissue after melting. Co‐delivery of ovalbumin (OVA)‐pulsed DCs (OVA‐DCs) and aPD1 via cryoMNs induced higher antigen‐specific cellular immune responses compared with the mono‐delivery of OVA‐DCs or aPD1. Finally, administration with cryoMNs co‐encapsulated with OVA‐DCs and aPD1 increases the infiltration of effector T cells in the tumor, resulting in stronger anti‐tumor therapeutic efficacy in both prophylactic and therapeutic melanoma models compared with administration with cryoMNs loaded with OVA‐DCs or aPD1. This study demonstrates the great potential of cryoMNs as a co‐delivery system of therapeutic cells and biomacromolecules for combinational therapies.